Egressos do programa brasil alfabetizado: desafios sobre continuidade de escolarização em EJA no Município de Conde/PB - Cavalcante, Arilú da Silva (2012)
This dissertation seek to investigate the motives which lead students who conclude the Literate Brazil Programme (PBA), in the municipality of Conde (State of Paraiba, Brazil) to continue (or not) their studies in youth and adult education programmes. Discussion on the continuity of schooling by means of youth and adult education (YAE) is developed within the perspective of Popular Education. We begin by analyzing the Decrees and Resolutions on the Literate Brazil Programme published by the Ministry of Education, reports from the State Forums of Youth and Adult Education and documents which deal specifically with youth and adult literacy in Brazil with a view to understanding current concerns and actions involving the continuity of studies by young people, adults and the elderly in the modality of YAE. We then analyze a number of theses and dissertations which deal with PBA with a view to identifying how the challenges with respect to the continuity (or not) of students who conclude PBA are dealt with in the different regions of the country. Finally we interview five students who concluded PBA, in the Municipality of Conde with the intention of identifying and analyzing their reasons for continuing to study. We dedicate special attention to the arguments capable of translating desires, aspirations and anxieties. To this end, we make use of Thematic Analysis, based on the Content Analysis approach (BARDIN, 2011). The works of Freire (2009, 2005, 1998, 1996,1979), Charlot (2005) and Pozo (2002) amongst others served as important references concerning the relation between knowledge and the active role of learners as a means of sustaining the schooling process in the modality of YAE. Amongst the results of the research we highlight: the interviewees consider teaching and learning as a means of creating good relations in the school context; they await urgent feedback, in the form of training, so that they can help the youngsters with home work, in order to obtain a national driving license, in order not to have problems in dealing with bank matters and in order to participate actively in church activities, among other practical demands.